Integrating an e-book Software with Vector Graphic Technology on Cloud Platform. (20th February 2015) - Chen, Tseng-Yi; Wei, Hsin-Wen; Cheng, Yu-Chun; Leu, Jenq-Shiou; Shih, Wei-Kuan; Hsu, Nien-I
Abstract: Many e-book applications have been available on the mobile devices in the recent decade. People read the electronic contents on their mobile devices. Meanwhile, a variety of mobile device platforms have emerged in the market. To make the e-book content compatible on different mobile device platforms, the layout or e-book application design needs to be adjusted based on the display resolution. However, different resolution settings are available in the mobile devices. For example, Android can runs on a variety of devices that offer different screen sizes. Android also can support different resolutions from 320*240 to 1280*720. Hence, the resolution becomes a critical problem for e-book content provider. Besides, image scaling is another problem for e-book applications. If the e-book application load bitmap images as its contents, the bitmap contents may be distorted when user scales up the size of contents or images. Therefore, the different resolutions and image scaling are two important issues in the design of e-book application. Vector graphic library can solve the above problems. However, vector graphic has bad performance in mobile devices and just few e-book contents are available in vector graphic format. Hence, file format conversion is another high-cost task in e-book with vector graphic. This paper proposes a cloud system integrating an e-book reader with vector graphic technology, called CloudVG. CloudVG optimizes the vector graphic library through a Renderscript method and offloads the conversion of bitmap to vector format on cloud platform. The experiment results show CloudVG can achieve 250% performance improvement over the original library and the procedure of file format conversion can achieve a near-linear speedup on cloud computing platforms.